Punishment in paradise: race, slavery, human rights, and a nineteenth-century Brazilian penal colony - Beattie, Peter M. (Duke University Press, 2015)
Fernando de Noronha Island: foil, paradox, paradise, or inferno? -- Getting to know "Fernando" -- "The key to the Americas?" -- Fernando de Noronha's "dark twins": licit and illicit commerce -- "Brothers of the peak": prosopography of a penal community -- The jealous institution and Brazilian penology -- "A stench in the nostrils of god?". The material and social life of exile -- Crime, conflict, corruption, and cooperation on an Atlantic frontier -- The treatment and categorization of slave convicts in a penal archipelago -- Of captivity and incarceration: human rights reform in Atlantic perspective -- Punishment in paradise foiled again